Analysis of social factors of the harry potter bullied In harry potter and the sorcere's stone Joanne kathleen rowling’s - Resti Hartika (Fakultas Sastra Universitas Ekasakti, 2017)
This research aims to analyze to illustrate the kind of bully action that do Dursleys, Draco Malfoy and Professor Severus Snape in Harry Potter. To describe the factors that trigger the Dursleys, Draco Malfoy and Professor Severus Snape take action against bully Harry Potter. To illustrate the social impact of the bully acts committed by the Dursleys, Draco Malfoy and Professor Severus Snape in Harry Potter in Harry Potter and the Sorcerer's Stone Joanne Kathleen Rowling. The method of the research is descriptive qualitative, which tries to explain about the correlations between author life background and its influence to the literary work produced. Sources of data in this study include the source of primary data and secondary data. Data collection techniques used in this study is a technique to read and record. The measures undertaken to analyze the data is as follows (1) Read the novel Harry Potter and The Sorcerer's Stone works J.K. Rowling. (2) Marking a sentence or a paragraph discussing about the social context associated with the bully action. (3) Analyzing the results about the social context are associated with the bully, the social picture, and social functions and (4) Describe results. After analyzing the social factors that Harry Potter bully (intimidated) in Harry Potter and the Philosopher's Stone, the author concludes the analysis into three findings: first to describe the type of action undertaken bully Dursleys, Draco Malfoy and Professor Severus Snape in Harry Potter. The types of bullying done of verbal bullying, where the actors perform intimidation through their words to a bully victim. Then bullying involving physical contact between the offender and the victim either directly or indirectly. This type of bullying usually include punching, kicking, slapping, choking, biting, spitting, even destroy the belongings of the victims, and relational bullying (friendship). Second to describe the factors that trigger the Dursleys, Draco Malfoy and Professor Severus Snape take action against Harry Potter bully. Factors child's own personal self, namely anxiety and feeling inferior from an agent, competition is not realistic, feelings of resentment arising from hostility or because the bullies had been the victim of bullying before, and the inability to handle emotions positively. Family factors namely lack of warmth and level of awareness of parents are low on his son, Pattern foster parents who are too permissive so that children are free to take whatever measures are desirable or otherwise. Factors association. Third to describe the social impact of the bully acts committed by the Dursleys, Draco Malfoy and Professor Severus Snape in Harry Potter. The social impact of the action bully among others They have a strong need to dominate and subdue other students and to get their own way. Are impulsive and are Easily angered. Are Often defiant and aggressive toward adults, Including parents and teachers. Show little empathy toward students who are victimized If they are boys, they are physically stronger than most other boys in general.